Implementation of Legal Protection for Victims of Revenge Porn Crimes Based on Law Number 31 of 2014 Concerning Protection of Witnesses and Victims from a Victimology Perspective - Dadang; Yusdiansyah, Efik; Darusman, Yoyon (Sinergi International Journal of Law, 2025)
This research is presented as a response to the rampant phenomenon of revenge porn, a cruel act that takes away privacy and causes deep trauma for its victims. This research seeks to examine more deeply about how the implementation of legal protection for individuals who are victims of revenge porn in Indonesia, especially within the framework of Law Number 31 of 2014 concerning Protection of Witnesses and Victims. Through the lens of victimology, this dissertation not only sees victims as passive objects in the justice system, but as individuals who have the right to comprehensive recovery and protection. This research explores further how legal protection for witnesses and victims can truly be felt by survivors of revenge porn, considering the unique characteristics of this crime that often leave deep psychological wounds and severe social stigma. To understand the reality of implementation in the field, this research uses empirical legal methods. This approach involves an in-depth analysis of relevant laws and regulations, combined with direct data collection from various related parties. In-depth interviews with victims of revenge porn, law enforcement officers, victim service institutions, and experts in the fields of law and psychology provide a window to understanding the challenges, obstacles and hopes in realizing effective legal protection for victims. The results of this study are expected to provide a complete picture of the extent to which Law Number 31 of 2014 has answered the protection needs of revenge porn victims. Moreover, this dissertation aims to identify gaps in implementation and formulate constructive recommendations. It is hoped that the findings of this study can contribute to collective efforts to create a legal system that is more empathetic and responsive to the suffering of revenge porn victims, as well as encourage the realization of true justice and recovery for them.